The pursuit of excellence : Kentucky State University, 1886-2020 - Hardin, John A., 1948- (Contemporary perspectives in race and ethnic relations., 2021)
"The Pursuit of Excellence: Kentucky State University, 1886-2020 is a compelling examination of the most diverse public institution of higher education in the Commonwealth of Kentucky. Starting with Kentucky State University's establishment in 1886 to train black school teachers, the book explored how the university met challenges and successfully overcame them. Although created in an era of racial segregation, Kentucky State University developed an inclusive faculty, staff and student body sustained by a tradition of academic excellence. By 2020, Kentucky State University offered bachelors, master's and doctoral degree programs as well as 1890 land grant research and service programs. The book provides background on selected notable alumni and their contributions to the Commonwealth and the world"--